FARMERS IN AGROECOLOGICAL TRANSITION: a study on marketing strategies - Mundo Neto, Martin; Fabbri Ramos, Raquel (Revista Interface Tecnológica, 2020)
This article deals with farmers who participate in Social Control Organizations (SCOs) a modality of organic certification provided for in Brazilian legislation for farmers in agroecological transition. The objective was to identify the marketing strategies of farmers belonging to 16 OCSs, located in different regions of the State of São Paulo, and to compare them with the propositions of the agroecology literature, verifying whether strategies that explore short commercialization circuits predominate. The data, referring to the year 2019, were collected in the National Register of Organic Producers (NROP), in interviews with farmers and representatives of local communities. Among the farmers of the 16 SCOs, direct sales strategies predominate, with emphasis on participation in organic fairs, organization of local consumer networks and participation in public calls related to institutional purchases. However, groups of farmers were identified in a fragile position with little insertion in local markets, and marketing was only part of their limitations.